Biodegradation of Malachite Green by Extracellular Laccase Producing Bacillus thuringiensis RUN1 - Olumide D. Olukanni,; Aliu Adenopo,; Ayodeji O. Awotula ,; Akinniyi A. Osuntoki, (Journal of Basic & Applied Sciences, 2021)
A bacteria strain Bacillus thuringiensis RUN1identifiedby 16s RNA gene phylogenetic analysiswas used to decolorize malachite green, a triphenylmethane dye in a simulated wastewater. The ability of the organism to produce extracellular laccase and degrade the dye were also investigated. Results showed that the organism decolorized (84.67 ± 1.19 %) malachite green at 40 mgl-1 within 6 h; and the decolorization was associated to laccase production by the organism experimentally. Laccase activity increased as the decolorization process progressed, with the highest activity value of 0.1043 ± 0.02 U/min/ mg protein recorded after 24 h of incubation using ABTS as substrate. In addition, FTIR analysis showed that the strain actually degraded the dye. It was therefore concluded that this strain of Bacillus thuringiensis will be relevant in the biotreatment of industrial effluent containing malachite green and in the production of laccase, an industrially important enzyme.